2021
DOI: 10.1177/00187208211033450
|View full text |Cite
|
Sign up to set email alerts
|

How Do Violinists Adapt to Dynamic Assistive Support? A Study Focusing on Kinematics, Muscle Activity, and Musical Performance

Abstract: Objective Assessing violinists’ motor and musical performance adaptations to dynamic assistive support (DAS) provided by a passive device, using a force-field adaptation paradigm. Background Up to 93% of instrumentalists are affected by musculoskeletal injuries and particularly violinists. The repetitive nature of their work may lead to muscle fatigue, an injury risk factor. DAS has been used in occupational settings to minimize muscle activations and limit fatigue accumulation. DAS may however affect motor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…High inter-trial repeatability of EMG measurements was observed in string players (violinists) with less than 10% deviation of the mean muscular activities from their averages over the repetitions 39 41 . Another study showed low variability in maximum mouthpiece forces and kinematics among trumpet players 42 .…”
Section: Discussionmentioning
confidence: 99%
“…High inter-trial repeatability of EMG measurements was observed in string players (violinists) with less than 10% deviation of the mean muscular activities from their averages over the repetitions 39 41 . Another study showed low variability in maximum mouthpiece forces and kinematics among trumpet players 42 .…”
Section: Discussionmentioning
confidence: 99%